Autoimmune thyroid diseases in patients on the vegan diet - Białczyk, Aleksandra; Stadler-Szajda, Justyna; Kamińska, Barbara (Journal of Education, Health and Sport, 2022)
Introduction and purpose: Autoimmune thyroid diseases are the most common thyroid dysfunctions. Among them, we distinguish entities such as Hashimoto's disease and Graves' disease. Diet is one of the environmental factors that may influence the onset and progression of autoimmune diseases. A vegan diet is characterized by the complete elimination of animal products and a greater supply of fiber, vitamins, and unsaturated fats. The study aimed to evaluate the influence of a vegan diet on the course of autoimmune thyroid diseases. A brief description of the state of knowledge: Numerous studies have shown significant changes in the severity of symptoms and blood laboratory parameters, as well as in the composition of the microbiota among people using only a vegan diet, which could indicate its protective effect on the body. However, an inadequately balanced vegan diet may predispose to deficiencies of key micronutrients such as vitamin B12 or iodine and selenium, so special attention should be paid to the appropriate balance of consumed products, especially in the case of people suffering from AITD. Conclusions: Reports from various studies may be the basis for developing a rational diet, which will be one of the elements of AITD prevention or treatment. It is essential to remember the proper balancing of meals that will ensure an adequate supply of microelements or vitamins, which is especially important in autoimmune thyroid diseases.